Curettage combined with decompression for the treatment of ameloblastoma in children: report of two cases - Chen Xu; Yuhua Hu; Yuhuan Sun; Qiang Shao; Yonghai Song; Jie He (BMC, 2024)
Abstract Background Ameloblastoma (AM) is the most common benign odontogenic tumor, which is more often detected in the mandible than maxilla, especially the mandibular body and mandibular angle. Pediatric AM is a rare disease, especially in patients aged 10 and younger. Compared with the mainstream osteotomy and reconstructive surgery for adult ameloblastoma, there is more room for discussion in the treatment of pediatric ameloblastoma. The postoperative functional and psychological influence can not be ignored. Especially for children in the period of growth and development, an osteotomy is often challenging to be accepted by their parents. We report two patients with ameloblastoma under 10 years old who are treated with curettage and fenestration, which is a beneficial method for children with ameloblastoma. Case presentation We present two cases of classic ameloblastoma in children. We describe in detail the patients' characteristics, treatment processes, and follow-up result. The bone formation and reconstruction in the lesion area after fenestration decompression and curettage are recorded at every clinic review. The surgical details and principles of curettage and decompression are also described and discussed. The two patients have good bone shape recovery and no recurrence. Conclusions Children are in the growth and development period and possess an extremely strong ability of bone formation and reconstruction. Based on the principles of minimally invasive and functional preservation, we believe that curettage combined with decompression can be the first choice for treating AM in children, especially for mandibular lesions.